Out‐Diffusion and Uphill‐Diffusion of Mg in Czochralski‐Grown (100) β‐Ga2O3 Under High‐Temperature Annealing and Its Influence on Lateral MOSFET Devices - Ta‐Shun Chou; Thi Thuy Vi Tran; Hartwin Peelaers; Kornelius Tetzner; Oliver Hilt; Jana Rehm; Saud Bin Anooz; Andreas Fiedler; Zbigniew Galazka; Martin Albrecht; Andreas Popp (Advanced Electronic Materials)
Abstract In this work, the out‐diffusion and uphill‐diffusion of Mg inside (100) β‐Ga2O3 epilayers and substrates are reported. The Mg accumulates toward the (100) surface upon annealing under an oxidizing environment, whereas the concentration profile changes with annealing temperatures and durations. Furthermore, the out‐diffusion of Mg from the substrate into the epilayer is observed at temperatures above 800 °C, which continues during the film growth. The substitutional‐interstitial‐diffusion (SID) mechanism is suggested to be the driving mechanism for the former, and the latter is related to the diffusion of mobile Mg interstitials. The accumulation profile of Mg can be used to identify the interface between the epilayer and the substrate. Furthermore, significant differences in device performance are observed for power transistors fabricated on annealed and non‐annealed epitaxial β‐Ga2O3 wafers. Increased breakdown voltages of annealed samples are attributed to the Mg diffusion into the first few nanometers of the epitaxial layer close to the interface to the semi‐insulating substrate, leading to compensation of residual dopants (donors) in that region.